Realita Penerapan Hukum Asas Praduga Tak Bersalah dan Hubungannya dengan Hak Asasi Manusia dalam Kasus Terorisme (International Forum of Researchers and Lecturers, 2024)
The principle of presumption of innocence aims to protect suspects or defendants from arbitrary actions by law enforcement officials. The principle of presumption of innocence is related to human rights. With this principle of presumption of innocence, the rights of those concerned must be respected. The person's human rights must continue to be protected by a fair legal process. In reality, the principle of presumption of innocence is often set aside in several cases, especially in cases of terrorism. How is the principle of presumption of innocence applied and its relationship with human rights in terrorism cases? And what needs to be done by the government to provide a legal umbrella to guarantee the application of the principle of presumption of innocence in law enforcement practices in terrorism cases? The method used by researchers here is the juridical method. Based on the results of research conducted by researchers, terrorism cases, which not only apply in Indonesia but also in other countries, are considered a crime that cannot be forgiven. The methods used by law enforcement are contrary to criminal justice and violate applicable laws. As a result, the existence of this principle is contrary to the reality that occurs in law enforcement practice. For this reason, it is necessary to carry out a review and take firmer action against law enforcement officials who do not heed the application of the principle of presumption of innocence, especially in cases of terrorism, in order to achieve the goal of just law amidst the dynamics of law enforcement. Keywords: , ,.